2003
DOI: 10.1002/jmv.10493
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of HBV DNA level and HBeAg titer in hepatitis B surface antigen positive mothers and their babies: HBeAg passage through the placenta and the rate of decay in babies

Abstract: It is well documented that perinatal transmission is the major cause of chronic HBV infection in China. However, the mechanisms of HBV perinatal transmission are not defined clearly. It is not known whether hepatitis B e antigen can cross the human placenta, and the rate of HBeAg decay in babies with and without HBV breakthrough has not been studied. In this study, HBV serological markers were investigated in 95 hepatitis B surface antigen positive pregnant women. These markers were also studied in the babies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
112
2
5

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(128 citation statements)
references
References 35 publications
9
112
2
5
Order By: Relevance
“…The mean serum HBV DNA level in the mothers of the infants with HBV breakthrough was significantly higher than in the mothers of babies who did not become infected. 35 Thus, he study concluded that HBeAg can cross the human placenta, and disappears from serum within 6 months in most babies. HBV DNA levels in hepatitis B infected mothers are associated with the failure of HBIg and vaccine immunization [see below], and the additional influence of transmitted HBeAg cannot be excluded.…”
Section: Risk Factors For Mother To Infant Transmission Hepatitis B Ementioning
confidence: 98%
“…The mean serum HBV DNA level in the mothers of the infants with HBV breakthrough was significantly higher than in the mothers of babies who did not become infected. 35 Thus, he study concluded that HBeAg can cross the human placenta, and disappears from serum within 6 months in most babies. HBV DNA levels in hepatitis B infected mothers are associated with the failure of HBIg and vaccine immunization [see below], and the additional influence of transmitted HBeAg cannot be excluded.…”
Section: Risk Factors For Mother To Infant Transmission Hepatitis B Ementioning
confidence: 98%
“…Epidemiologic reviews indicate that Asian patients generally undergo HBeAg seroconversion at a median age of 35 years. Viral clearance occurs at an estimated annual incidence of 2-15% [25,26]. In a cross-sectional analysis of 544 women, aged 18-50 years, with CHB, who were followed in a district hospital in Hong Kong, 38.4% were HBeAg positive and 61.6% were HBeAg negative [27].…”
Section: Prevalence Of Chb Among Asian Women Of Childbearing Agementioning
confidence: 99%
“…8,9 Both infected and uninfected infants have been shown to encounter HBeAg in utero, but exposure to hepatitis B core antigen (HBcAg), which would indicate possible exposure to virions, has not been documented in babies of either HBeAg 1 or HBeAg 2 mothers. 8,10 Prevention of mother-to-infant transmission has been largely achieved by the administration of passive hepatitis B immunoglobulin and active immunoprophylaxis to all neonates born to carrier mothers. However, the added benefit of passive immunoprophylaxis in newborns of HBsAg 1 /HBeAg 2 carrier mothers has recently been questioned.…”
Section: Introductionmentioning
confidence: 99%